An Innovative Passivation Technique for Enhanced Corrosion Resistance of Zinc Coatings - Usta, Ibrahim; Ciftci, Muhammed Furkan; Gur, Emine; Kahveci, Hulyanur (Pleiades Publishing Ltd, 2024)
This study introduces an innovative passivation technique designed to improve the corrosion resistance of zinc coatings. The impact of varying sodium silicate concentrations (4, 6, and 8 mL/L) and passivation times (30-90 s) was examined in baths containing Cr+3 and Co+3 ions. The 120-h salt spray test results revealed that the optimal corrosion resistance was achieved with a medium sodium silicate concentration of 6 mL/L and a 30-s passivation time. This combination led to a significant improvement in performance, with only 12% white rust observed after 120 h. The study highlights the importance of optimizing treatment parameters to significantly enhance corrosion resistance. Notably, Simonkolleit was obtained at a high concentration of 6 mL/L and a 30-s passivation time, further contributing to the enhanced durability of the coating. These surface enhancements provide a promising approach for achieving durable and more efficient zinc coatings in industrial applications.
Keywords: zinc coating; sodium silicate; passivation corrosion; simonkolleite; salt spray test